Consumers acceptance of new food ingredients from the food industry’s by-products—a focus group study - Scheibenzuber, Sophie; Pucci, Emilia; Presenti, Ombretta; Serafini, Giacomo; Nobili, Chiara; Zoani, Claudia; Duta, Denisa Eglantina; Mihai, Adriana Laura; Criveanu-Stamatie, Gabriela Daniela; Belc, Nastasia; Falch, Eva; Rustad, Turid; et al. (Frontiers in Nutrition, 2025)
Food industry by-products can be valorized by extracting various nutritional components, like proteins, dietary fiber or other bioactive compounds, depending on the type of by-products. By adding these to new or already existing food products, the consumers’ health and wellbeing may increase due to a more nutritional diet while at the same time increasing the sustainability of the food chain. However, for a successful market implementation of products containing ingredients from by-products, the consumer perception and consumer acceptance are one of the most important aspects that need to be considered. Therefore, focus group studies were organized in four European countries, namely Italy, Germany, Romania and Norway, to investigate the perception, acceptance and willingness of the general population (ages 18–60) to buy these new products. When possible, individual purchasing and consumption trends were analyzed as well to get a deeper insight into the decision-making processes during grocery shopping. In summary, the acceptance of new food ingredients from by-products was high in all four studied countries, and most participants were interested in enriched bakery, meat or dairy products. The main reason for the interest in these new products were health benefits due to an increased nutrient uptake, and to contribute to reducing food waste. However, participants were afraid of new food allergies and intolerances as well as increased concentrations of food contaminants like pesticides or mycotoxins, which makes food safety an important point to consider before developing new products.